2022
DOI: 10.54548/njps.v37i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes in Serum Calcium, Phosphate, Vitamin D, Parathyroid Hormone and Calcitonin During Pregnancy and Lactation in Randomised Population of Zaria Women

Abstract: Pregnancy and lactation are usual but stressful physiological conditions accompanied by changes in calcium and phosphate metabolism and their regulatory hormones which may lead to calcium-related disorders in pregnant women. This study aimed to evaluate the changes in serum levels of calcium, phosphate, vitamin D and their regulatory hormones in pregnant and lactating women in Zaria, Nigeria. A cross‑sectional descriptive study was conducted at Ahmadu Bello University Teaching Hospital, Zaria for three (3) mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Zhang et al, 2014 demonstrated that vitamin D supplementation in pregnant women resulted in increased GSH levels and a significant difference in plasma MDA levels. Asemi et al (2014) had previously presented data in support of this, revealing that vitamin D supplementation significantly increased GSH levels just as There was strong negative correlation between vitamin D and calcium as well as vitamin D and phosphate (Avidime et al 2022).…”
Section: Discussionmentioning
confidence: 71%
“…Zhang et al, 2014 demonstrated that vitamin D supplementation in pregnant women resulted in increased GSH levels and a significant difference in plasma MDA levels. Asemi et al (2014) had previously presented data in support of this, revealing that vitamin D supplementation significantly increased GSH levels just as There was strong negative correlation between vitamin D and calcium as well as vitamin D and phosphate (Avidime et al 2022).…”
Section: Discussionmentioning
confidence: 71%